Óleos essenciais de plantas brasileiras - Alencar, R. de; Lima, R. Alves de; Corrêa, R. G. Campos; Gottlieb, Otto R.; Marx, M. C.; Silva, M. Leão da; Maia, J. G. Soares; Magalhães, Mauro Taveira; Assumpção, R. M. Viegas (Acta Amazonica, 1971)
As part of a chemical survey of brazilian plants, we report the presence of essential oils in the wood of Dicypellium caryophyllatum Nees (Lauraceae), composition: eugenol 95,5%, O-methyleugenol 1,6%; the leaves of Myrcia polyantha D.C., var. coriacea Bg. (Myrtaceae), yield: 2%, composition: limonene 4,5%, neral 28,0%, geranial 50,2%, sesquiterpenes 14,6%; the bark of Parkia oppositifolia Spr. ex Benth. (Leguminosae-Mimosoideae). composition: methyl salicylate 98,2%; the trunk wood of Dalbergia decipularis Rizz. et Mattos (Leguminosae-Papilionatae), composition: nerolidol 97,2%; the trunk wood of Poecilanthe parviflora Benth. (Leguminosae-Papilionatae), composition: nerolidol 26,0%; the leaves of Piper cavalcautei Yuncker (Piperaceae), yield: 1.9%, composition: safrol 69,0% methyleugenol 8,0% terpenes 23,0%.